The Scope and Nature of Urban Research in Australia - King, Herbert W. (ERDKUNDE, 1955)
The following paper reports on the diverse body of writing on Australian cities and attempts to explain why urban geographic research in this continent has been relatively neglected compared to that of other countries, e.g., European countries and the United States. Popular publications on Australian cities are quite common. In addition, there is a growing body of research on urban history and on individual traits of urban life. Detailed reports by urban planning bodies have also recently become more numerous. But the amount of urban geographic literature in the proper sense is still very small. The urban geographic works on Australian cities can be divided into 2 groups: 1. descriptive works on urban development, urban morphology and urban functions, 2. analytical studies, which basically deal with the problems of site conditions and the functional tasks of the capitals (of the states), especially Sidney. The absence of an extensive urban geographic literature seems to be due to 2 causes: 1. the few geographers engaged in scientific work are faced with the great task of dealing with the total field of geography of an entire continent; 2. the nature of the continent itself has directed geographical research more toward physical and economic than social problems.